The enthronement of compassion and care and the unseating of customary obligation in the parable of the Good Samaritan - F. Dagmang (Acta Theologica)
The article studies the parable of the compassionate and caring Samaritan as source of radical lessons in dispensing care. In the parable, Jesus stressed that the dispensing of care should be primary and conformity to customary obligations are to be subordinated. This study primarily examines the power of obligatory customs that Jesus “overpowered” and attempts to elaborate on the following reasons why Jesus had to dethrone customary obligations. First, traditional customs turned prejudices have debilitating effects on character, behaviour, and moral agency. Secondly, overcoming negative prejudices will free our minds for creative responses and lead us toward a better understanding of compassionate care as possessing a divine character.